Sistem Pengelolaan Arsip Surat Masuk dan Keluar Berbasis Client Server Studi Kasus: SMK N 1 MANDIRAJA - ABDUL AZIS (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Archive incoming and outgoing mail for this is still done conventionally in the form of hard copy or sheets of paper are difficult in terms of search at any time if needed. Incoming mail a few years ago would be difficult to find if usung hard-copy storage means either that because of the accumulated records orarchives because the letters that have been damaged. Difficulties and complexities can be overcome by building a more structured mail archive administration system so that it can speed up existing data searches and report generation, so the authors feel the need to design a Client Server-based Administration System Management using the PHP programming language and MySql database. Methods in collecting data in this research were observation, interview, literatur interview, and documentation. System development method used is Extreme Programming. Administration System Management of this mail archive can be used to simplify the process of searching, reporting and managing file records at Vocational High School Negeri 1 Mandiraja.